CAUSES AND COMPLICATIONS OF DIABETES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article provides information about diabetes, its causes, and the changes and symptoms that occur in the cardiovascular system due to this disease. This disease develops slowly and suddenly leads to severe complications. In the beginning, symptoms such as dry mouth, thirst and weight loss are not obvious. The patient is more disturbed by weakness, fatigue and thirst. Despite the high level of glucose in the blood, in type 2 diabetes, the amount of acetone cells in the blood increases, and its appearance in the urine is very rare. Such patients can live without taking insulin. they can use diet, exercise, and blood sugar-lowering medications[1,2].